Who Watches the Watchers - Labkoff, Steven E.; Sittig, Dean F. (Applied Clinical Informatics, 2017)
The rise in the use of electronic health records (EHRs) and associated resources over the last decade is leading to the end of the paper medical record and all the risks associated with the use of a paper chart. However, there has not been a concomitant creation of a systematic oversight body that is specifically charged with ensuring the public’s safety through the use of EHR knowledge resource tools or EHRs themselves. We recommend the formation a Health Information Technology Safety Center. Such a center could collect error reports, review EHRs and the knowledge resources incorporated within them, and investigate particularly challenging EHR-related safety issues at participating health care delivery organizations. Safety issues could be identified, corrected, and the solutions widely disseminated.Citation: Labkoff SE, Sittig DF. Who watches the watchers: working towards safety for EHR knowledge resources. Appl Clin Inform 2017; 8: 680–685 https://doi.org/10.4338/ACI-2017-02-IE-0032